Analysis of early relaparotomy in recipients of adult living donor liver transplantation - Gokhan Ertugrul; Atıf Tekin; Mahmut Zenciroglu (Archives of Organ Transplantation - Peertechz Publications, 2021)
Background: While early relaparotomy following living donor liver transplantation (LDLT) is an important event and its outcomes are still unclear, the aim of this retrospective study is to investigate the causes and outcomes of early relaparotomy in recipients of adult living donor liver transplantations. Materials and methods: Between April 2015 and April 2020 at Medipol University Medical Faculty Hospital Organ Transplantation Department, Istanbul, Turkey, 15 patients (9.3%) who underwent early relaparotomy were studied retrospectively.  Results: Eight patients (53.3%) had a history of upper abdominal surgery in the early laparotomy group. The most common cause of early relaparotomy had postoperative bleeding in 9 patients (60%). The overall survival rate was 66.7%. Mortality was higher in the group over 60 years old and with a history of upper abdominal surgery. Conclusions: The history of upper abdominal surgery appears to be a risk factor for early relaparotomy. Also, previous upper abdominal surgery group and elderly patients group present with more mortality. We should be very careful in these groups.